Reagan Louie : sex in Asia. - Louie, Reagan; Quan, Tracy; San Francisco Museum of Modern Art, San Francisco (New York : powerHouse Books Brooklyn, 2003)
The photographs of Reagan Louie presents an artist's candid and complex study of the contemporary Asian sex industry. With subjects ranging from Thai sex emporiums to Japanese image clubs to Taiwanese betel nut stands, Louie's pictures explore this thriving trade and the fantasies it nourishes.
korte biog. p. 191
Engels
Exhibition. Reagan Louie : sex in Asia. SFMOMA (San Francisco Museum of Modern Art) San Francisco. 2003-09-04. 2003-12-07
boek
Keywords: Louie, Reagan; Azië